Procesamiento de imágenes a partir de muestras de imágenes provistas de una cámara en tiempo real utilizando visión artificial - Martínez Cuenca, Diego Fernando (2016)
With the growing computer insecurity the security of information or access to places which prior an authorization is required, it has become an important in public and private sectors. Although many technologies have been developed to control access to files or resources, to enforce security policies, and to audit network usages, there does not exist a stable technology free that can verify that the user who is trying to enter at the system is the same person who logged in. The Facial Biometric System has been adopted to monitor the presence at the time of authentication. Therefore, only the legitimate user could be registered and unauthorized entities have less chance to hijack the register. The aim is to provide a new security option by recognizing the human face in real time as it is unique to each person.